2020
DOI: 10.1097/aln.0000000000003550
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Trial of Platelets Stored Cold versus at Room Temperature for Complex Cardiothoracic Surgery

Abstract: Background This pilot trial focused on feasibility and safety to provide preliminary data to evaluate the hemostatic potential of cold-stored platelets (2° to 6°C) compared with standard room temperature–stored platelets (20° to 24°C) in adult patients undergoing complex cardiothoracic surgery. This study aimed to assess feasibility and to provide information for future pivotal trials. Methods A single center two-stage explor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
74
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(76 citation statements)
references
References 23 publications
2
74
0
Order By: Relevance
“…12 Importantly, the first contemporary clinical trial of coldstored platelets transfused units supplemented with PAS (PAS-C and PAS-E), and reported that they performed similarly to RT platelets for the treatment of bleeding in cardiac surgical patients. 44 While these studies provide essential insight, they also highlight the need for a greater understanding of the impact of storage solution on platelet quality during cold-storage.…”
Section: Discussionmentioning
confidence: 99%
“…12 Importantly, the first contemporary clinical trial of coldstored platelets transfused units supplemented with PAS (PAS-C and PAS-E), and reported that they performed similarly to RT platelets for the treatment of bleeding in cardiac surgical patients. 44 While these studies provide essential insight, they also highlight the need for a greater understanding of the impact of storage solution on platelet quality during cold-storage.…”
Section: Discussionmentioning
confidence: 99%
“…Both studies agree that CSPs are a useful alternative to RT platelets and could be even more effective in a post-traumatic context, where speed and strength of clot formation has priority. A recent pilot trial supports the feasibility of platelets stored cold for up to 14 days and provides critical guidance for future pivotal trials in high-risk cardiothoracic bleeding patients [ 77 ].…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Torres and colleagues demonstrated in a rat hemorrhage model that CSP participated equally in clot formation when compared to room temperature platelets (79). A randomized clinical trial in Norway demonstrated that 7 day CSP transfusion is at least equally as effective as room temperature platelets in treating post-operative bleeding after cardiac surgery in people (80). When paired with the logistical superiority of prolonged storage life and decreased risk of bacterial contamination, the functional equivalence of CSP prompted the military to request an FDA variance allowing 14 day cold storage of platelets.…”
Section: Chilled Plateletsmentioning
confidence: 98%